ABUNDANCE OF SEA CUCUMBER SPECIES IN THE COASTAL WATERS OF NUSI ISLAND, NABIRE REGENCY, CENTRAL PAPUA PROVINCE: KELIMPAHAN SPESIES TERIPANG DI PERAIRAN PESISIR PULAU NUSI, KABUPATEN NABIRE, PROVINSI PAPUA TENGAH - Paulus Boli; Zainab Lahaji; Gandi Yantri Sevantina Purba; Vera Sabariah (Jurnal Teknologi Perikanan dan Kelautan, 2026)
The intertidal zone of Nusi Island, Nabire Regency, is a habitat for sea cucumbers. Nusi Island is part of a group of small islands administratively located in Makimi District and is privately managed by the Kipuw family, implementing the “sasi” customary system, which regulates resource utilization. This study aims to identify sea cucumber species and analyze their abundance on Nusi Island as baseline information for island owners and local government. The study was conducted from June to August 2023. A total of 13 sea cucumber species were identified, belonging to four genera: Holothuria (four species), Bohadschia (six species), Pearsonothuria (one species), and Actinopyga (two species). The abundance of sea cucumbers in the first, second, and third observations was 91 individuals/250 m² (0.36 individuals/m²), 49 individuals/250 m² (0.20 individuals/m²), and 37 individuals/250 m² (0.15 individuals/m²), respectively. The mean total abundance of sea cucumbers on Nusi Island was 177 individuals per 250 m² (0.71 individuals/m²). The highest relative abundance was found in the sand sea cucumber (Holothuria scabra), followed by the banded sea cucumber (Actinopyga bannwarthi), while the eyed sea cucumber (Bohadschia ocelata) showed the lowest relative abundance. The relatively even distribution of individuals among species suggests that the sea cucumber community structure is comparatively stable and well-balanced. Environmental parameters, including pH, salinity, and temperature, were within the appropriate range for sea cucumber survival. This study provides baseline data to support the designation of conservation or limited-use zones and to guide sustainable sea cucumber management within an integrated coastal management (ICM) framework.